Madweng Pottery Tradition in Santa Maria, Isabela - Geronimo, R R (KnE Social Sciences, 2018)
This study investigates the unique indigenous pottery traditions of the Madweng in an Ibanag community in Santa, Maria, Isabela, located in the interior northwestern part of the province of Isabela, Philippines which boasts its huge non -metallic deposit of clay. The Madweng are the Ibanag potters who make, produce such earthenwares. Ethnography as a research design and strategy is utilized to understand indigenous concepts, technology and pottery traditions in manufacturing the dweng. Ethnographic methods like interviews, fieldwork, recording of field notes, direct observation, and smartphones were used for photographs, audio recording and analyzing data. Utilizing mga katutubong metodo sa Sikolohiyang Pilipino (methods in Filipino Psychology) the indigenous method of pakikipagkuwentuhan” (sharing stories), and pagtatanongtanong (asking around), the Ibanag language was employed to draw information in the indigenous idea of pagpapakuwento” (someone is telling the story). Results showed that Ibanag pottery tradition was introduced by the Kalingas, kept and used as a significant part of an Ibanag heritage from their ancestors. Manu-mano or hand modelling, maffulang or painting, magabba or firing, were some parts of indigenizing methods by the Madweng. Since 1954, no major changes in the method of manufacture from the teachings of the Kalingas except for a minimal technological advancement in manufacturing pots using the hurmaan, or molder. There is a need for intervention of Local Government of Santa Maria to revitalize the community based cooperative and maintain a sustainable livelihood program to hone the skills and uplift the Madweng economic condition. Keywords: dweng, Ibanag, indigenous pottery, madweng, Santa Maria